Efforts to Increase Efficiency at the Rspad Gatot Soebroto Nuclear Medicine Installation Using the Icor Method - Oviyan Patra; Aris Lambang; Hendy Suryana (International Journal Labs, 2025)
Gatot Soebroto Hospital, as a leading hospital in Indonesia, faces challenges in optimizing the use of resources, particularly in the Nuclear Medicine Installation, where the increase in the number of patients is not matched by proportionate revenue growth. This research aims to enhance operational efficiency at the RSPAD Gatot Soebroto Nuclear Medicine Installation by utilizing the Incremental Capital Output Ratio (ICOR) method. The research method employs a quantitative approach with time series data analysis of financial statements from 2020 to 2024, complemented by semi-structured interviews. Despite advancements in medical technology, the hospital struggles with resource optimization, particularly the mismatch between patient volume growth and income generation. Through a comprehensive analysis, the study identifies inefficiencies in capital utilization and proposes lean management principles to minimize waste in hospital processes. The findings reveal fluctuations in investment efficiency, with recommendations for prioritizing impactful investments, optimizing digital systems, and improving collaboration with third parties. This research contributes to both theoretical understanding and practical applications for enhancing hospital performance.